Aperiodical corelation function and complexity (Equivalen linear sapan) of the nonlinear PN-sequences for 3. generator CDMA. - Lâm, Nguyễn Văn; Quỳnh, Lê Chí; Sơn, Nguyễn Vũ (Journal of Computer Science and Cybernetics, 2012)
-